Professional Communicative Competence as a Key Component of the Foreign Language for Specific Purposes Course Design. - Mudra, Olena; Mudra, Olena (Видавничий дім «Гельветика», 2023)
Following the steps of improving the quality of higher education, this article focuses on the development of professional communicative competence of the future Information Technology specialists, consisting of intercultural, humanities, social and linguistic components. In this context learning Foreign Language for Specific Purposes, which enables students to adapt quickly to new challenges of academic and professional communities, is becoming very important – provoking interest not just among university teachers but also among learners. Analysing the programs of universities in different countries, we came to the conclusion that the appropriate Foreign Language for Specific Purposes course design could solve the issue of the development process. The historical background of foreign language learning for specific purposes, its development as a branch of applied linguistics, and potential directions for further research is also presented in this article. The basic objectives, content and learning tools professional foreign language communication are defined and generalized. It has been made an investigation in the sphere of professional communicative competence of the future IT specialists and made an attempt to develop a model of the successful course. The survey among the students (future Information Technology specialists) was conducted and analysed to determine the key components of the course activities. It was found that the content of professional foreign language communication is an organic component of higher education. The professional skills and abilities of the future Information Technology specialists in the field of intercultural language communication are substantiated. Taking into consideration the relevant experience of teaching Foreign Language for Specific Purposes, was made an attempt to develop a model of the successful course design. It is proved that the course development should be based on strong collaboration between the subject specialists (IT experts) and the language teachers. A hypothesis is put forward regarding the foreign language teachers need to gather all necessary information about a student’s subject course, decide how teaching Foreign Language for Specific Purposes fits to their course and what priorities does the department and students could see.
Keywords: Higher education; IT specialists; Foreign Language for Specific Purposes; Professional communicative competence; Course design; Intercultural communication